Reconstruction of Tax Case Investigations to Avoid Business Crimes Based on Legal Certainty - Harahap, Siti Holija; Mansar, Adi; Eddy, Triono (Faculty of Law, Universitas Pekalongan, 2024)
Based on the tax revenue report submitted by the Minister of Finance, it is necessary to improve professionalism in managing state finances, especially when related to taxation. In addition to professionalism, supervision also needs to be improved, both preventive and repressive, to prevent deviations or abuse of office in managing state finances, especially related to tax management. The criminal law policy in the field of taxation in the future should be in line with the principle of criminal taxation,